CPWF Medium Term Plan (2007-2009) - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2006)
This introductory section covers the period since the submission of the last Mid-Term Plan until present, and concentrates on the following areas: > Principal areas of progress. > Developments in 2005 and early 2006. > Changes to the CPMT strategic plan. > Research achievement highlights. > Program progress. At this point – just under half way (two years and six months) in the implementation of the first CPWF phase (and three-and-a-half years since inception began) governance and management processes are running smoothly, the program is in reasonable financial health, and technical processes – such as issuing new calls and obtaining reviews by the CPWF Expert Panel on Scientific Quality – are familiar, although they must be adjusted to each specific instance. Fifty-two projects – from the first competitive call, Basin Focal Projects (BFPs) and small grants for impact - are contracted and funded. All but six of the fifty-two were selected competitively by the CPWF. Some have been running nearly two years, but a majority are one year old or less. Early results – and better understanding about the details of results that can be expected – are beginning to flow. Synthesis research – a major and important challenge, and the key to the added value of the program – is also beginning to function. A second competitive call is very important strategically to “fill gaps” in the initial CPWF research portfolio and to maintain interest and momentum. The challenge has been to obtain sufficient funding alongside other important demands, especially the BFPs. An increased contribution from the World Bank for 2006 and confirmation of likely funding from the European Commission for 2006 has enabled a modest second call to be initiated. A call for concept notes is currently advertised. The call and priorities are available on the CPWF web page www.waterandfood.org. Working from gaps identified by CPWF theme leaders (TLs) and basin coordinators (BCs) in previous CPWF priorities and from summaries specially contracted by the CPWF from the Comprehensive Assessment on Water Management in Agriculture (CA), TLs and CPWF Management Team (CPMT) prepared a focussed set of priorities that was submitted for review to the CPWF Expert Panel. At the CSC meeting held in Cairo (May 2 – 3), the CPWF Steering Committee confirmed six research priorities to focus the second call. Each project will have a funding ceiling of US$ 0.5 million and will be expected to deliver results in two years, to coincide with the completion of the CPWF’s first phase.